2021
DOI: 10.1186/s13023-020-01577-4
|View full text |Cite|
|
Sign up to set email alerts
|

Long-term survival with sebelipase alfa enzyme replacement therapy in infants with rapidly progressive lysosomal acid lipase deficiency: final results from 2 open-label studies

Abstract: Background If symptomatic in infants, the autosomal recessive disease lysosomal acid lipase deficiency (LAL-D; sometimes called Wolman disease or LAL-D/Wolman phenotype) is characterized by complete loss of LAL enzyme activity. This very rare, rapidly progressive form of LAL-D results in severe manifestations leading to failure to thrive and death, usually by 6 months of age. We report results from 2 open-label studies of enzyme replacement therapy with sebelipase alfa, a recombinant human LAL,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 15 publications
5
36
1
Order By: Relevance
“…Most of our patients (4/5) experienced no medically relevant infusion-associated reaction (IAR) during the follow up, thus confirming the acceptable safety profile of the product [ 17 ]. One patient had one medically relevant IAR justifying systematic infusion premedication.The anaphylactic reaction presented by the patient might be favored by the absence of sebelipase alfa titration (i. e. the patient received a 5 mg/kg sebelipase alfa infusion as first dose compared to progressive increase of the dose for the 4 other patients).…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…Most of our patients (4/5) experienced no medically relevant infusion-associated reaction (IAR) during the follow up, thus confirming the acceptable safety profile of the product [ 17 ]. One patient had one medically relevant IAR justifying systematic infusion premedication.The anaphylactic reaction presented by the patient might be favored by the absence of sebelipase alfa titration (i. e. the patient received a 5 mg/kg sebelipase alfa infusion as first dose compared to progressive increase of the dose for the 4 other patients).…”
Section: Discussionsupporting
confidence: 62%
“…WD is an ultrarare disease leading to death before 12 months of age if untreated [ 8 ]. Sebelipase alfa ERT trials reported 68% survival at 5 years [ 17 ] but long-term follow-up in real-life settings are lacking. Here, we report the bio-clinical evolution of 5 WD patients treated with sebelipase alfa up to 10 years and we confirm its strong efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our analysis for liver volume change, the overall pooled reduction was not statistically significant; however, all three individual studies have reported a significant decline with the sebelipase intervention. 15,16,18 Here too, Jones et al…”
Section: Change In Other Efficacy Measuresmentioning
confidence: 98%